Minangkabau philanthropy: The spirits and behaviours of generosity of the Nagari communities in facing natural disasters - Nopriyasman Nopriyasman; Asnan Gusti; Ferdinal Ferdinal; Zahid Indirawati; Harits Ritonga Abdul (E3S Web of Conferences)
The world of philanthropy in traditional societies reflects communal behaviour in ensuring the social life of adat communities in Nagari. The historical aspects of philanthropy are crucial in revealing the values that guide social communities in facing natural disasters. This study explores the historical values of traditional societal behaviour in philanthropy, driven by Minangkabau history, cultural expressions, and the reality of social practices. The research follows historical methods and historical thinking stages. It employs a qualitative approach within a multidisciplinary framework (history, culture, and language), and quantitative approach through questionnaire. The findings show that philanthropic practices foster solidarity within Nagari communities and among their diaspora members. This bond is reflected in traditional charitable behaviours based on empowering the Nagari community’s identity through historical, cultural, and religious ties to ensure survival during calamities. Local philanthropy in disaster-affected areas strengthens in terms of volunteer labour, while financial aid increases among unaffected communities beyond and diasporas. This study is valuable for maintaining social integration, solidarity, social justice, togetherness, and a shared sense within adat communities and for the active participation of the Minangkabau people in particular and Indonesians in general.